Remarks by World Bank Group President David Malpass at the G20 Finance Ministers and Central Bank Governors Meeting Held During the 2022 Annual Meetings - Malpass, David (Washington, DC: World Bank, 2022)
This report discusses the remarks delivered by World Bank Group President David Malpass at the G20 Finance Ministers and Central Bank Governors meeting held during the 2022 annual meetings. He discusses: the world needs to be much better prepared to respond to pandemics, catastrophes, and health emergencies. Investing in prevention and preparedness now will save lives and, over the medium term, will save resources. Since the COVID-19 pandemic is not yet behind us, let me first say a few words about our efforts to support countries through this pandemic. I’ll then turn to the topic of preparedness and financing for future health crises. The World Bank Group’s 157 billion dollars response to COVID-19 was unprecedented. It was the fastest and largest growth in our history. This helped countries evaluate their health capacity gaps, finance their health systems, secure vaccines, and turn those vaccines into actual vaccinations in the poorest countries. As of last week, our financing has helped 67 countries purchase over half a billion doses. Doses closely connected. The doses are closely connected to our financing of country deployment programs and monitoring, through workforce training, public awareness campaigns, logistics, cold chain capacity, syringes, and testing kits. Preparedness and building for the future are core to the World Bank’s mission through comprehensive health projects. We are working to strengthen health systems in over 100 countries with an active portfolio totaling 30 billion dollars.